Noticing as reasoning in Lesson Study teams in initial teacher education. (May 2022) - Bakker, Carien; de Glopper, Kees; de Vries, Siebrich
Abstract: In the current study on noticing as reasoning of Lesson Study (LS)-teams in initial teacher education (ITE), we analyzed the reasoning two mixed LS-teams set up about pupils' subject-related learning of. Both teams consisted of a student teacher and experienced teachers. Both teams paid more attention to identification (describing pupils' learning behavior) and planning elements (considering and deciding how to act) than to interpretation elements (determining and explaining pupils' problems with learning). They differed in the extent to which they considered plans and provided continuity in their reasoning. Stimulating meaningful reflection may help further develop noticing among LS-teams in ITE. Highlights: The analysis approach developed for this study helps reconstructing noticing as reasoning during LS-conversations. Two mixed LS-teams in initial teacher education reason about learning, teaching and mixed problems. The two mixed LS-teams provide their reasoning with similar elements. Both LS-teams pay more attention to identification and planning than to interpretation elements. Both LS-teams differ in foci, extent of planning considerations, and continuity in their reasoning.